Images of the Invisible: Composite Photography and Proust's À la recherche du temps perdu. (1st December 2008) - Larkin, Áine
Composite photography provides a plausible model for Proust's perspective on the related processes of perception and memory. In addition, the function of the composite photographic image in exposing the invisible or in making essence perceptible can be linked not only to Proust's perspective on time and on transience, but also to the revelatory potential of metaphor and art, a potential based in great part on the tension between absence and presence and between invisibility and visibility.